DETERMINAN PERTUMBUHAN EKONOMI DI PROVINSI BANTEN - Manurung, Wahyudi; Fajar, Muhammad; Noviar, Noviar (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2022)
Economic growth is one of the important indicators in ensuring the continuity of economic development and improving the welfare of a region. Although there have been many studies conducted at home and abroad on economic growth, not many studies have examined economic growth in Banten Province. This study aims to analyze the factors that influence economic growth in Banten. Data used in this paper are gross regional domestic product based on constant prices as a proxy for the economic growth, human development index (HDI), number of workers, degree of trade openness, gross fixed capital formation and actual government expenditures sourced from Statistics Indonesia (BPS). The method used in this sudy is panel data regression analysis at the cities level in Banten for 2010 to 2019. The results indicate that the human development index (HDI), number of workers, degree of trade openness and gross fixed capital formation have significant effects on economic growth. In contrast, actual government expenditures no significant impact on economic growth in Banten. .